Management of inventory as fact fundamental for alive on marketplace: analysis through application of Proknow-C - Santos, André Luís Kimura; Servare Junior , Marcos Wagner Jesus; Bernardina, Fernanda Pecemilis Dalla (Brazilian Journal of Production Engineering, 2022)
The research in focus has the purpose of demonstrating that the ProKnow-C methodology contributes to assisting in the elaboration of the bibliographic portfolio, consequently making the researcher’s study about the pre-selected topic objectively more efficient and practical. Doing several filtering processes, reading the titles, abstracts and integrals of the articles, they made the author arrive at 12 articles that make up the bibliographic portfolio. The research found the place of published articles, number of citations, year published, main methods and tools used and applied and their contributions in relation to the results that each article obtained for the improvement, optimization of processes and cost reduction that the poor management of stock was causing.